Input : Output Exploring Participatory Art Practice from Within - Elly Kent (Graduate School of Institut Seni Indonesia Yogyakarta, 2014)
This paper explores the theory, practice and ongoing outcomes of two projects in relational/dialogical/participative art, narrated from two subjective perspectives: that of a participant, and that of artist. The two projects explored are FX Harsono’s “In Memory of a Name Curatorium” and my own resulting project “Nee (Born As).” This paper positions contemporary participatory art practice as a medium, through which differing cultural perspectives can be explored. In this model, methodology is a kind of a neutral construction -uncultured- to which artists and participants apply their own experiences of culture and context, extracting raw data from which creative responses emerges. Input: output.